Anatomical Variation in Origin of Profunda Femoris Artery and its Branches - Shambhu Nath Jha; Saif Omar (Academia Anatomica International, 2019)
Introduction: Profunda femoris artery (PFA) is the leading branch of femoral artery which supplies all the muscles of thigh. During the procedures arterial catheterization damage to PFA may invite unnecessary and unpredicted complications. Precise anatomy of PFA forms strong foundation to minimize problems. The aims of the present study were to compare the right side and left side origin of profunda femoris artery cross sectional area, and to compare the distance of origin of the femoral artery branches from mid-inguinal point. Subjects and Methods: The study was conducted in Mata Gujri Memorial Medical College, Kishanganj, Bihar. This study based on dissections performed on 60 properly embalmed human cadaver specimens. All the mode of origin and its level calculated using statistically parameters and equations. The specimens with range between 21-60 mm in diameter were included for the study in left and right side origin level of PFA identified. Results: In the present study out of 60 a total 56 specimens screened for dissected lower limb specimens. The 52 had arising separately from femoral artery, 3 specimens arising as a common trunk with medial circumflex femoral artery, and 1 patient arising s common trunk lateral. Higher level of level of origin of PFA was found to be quite recurrently. The different type of range were observed in lateral circumflex femoral arteries and medial circumflex femoral arteries from right and left sides of arteries. The range between 21-30 mm diameters were successfully noted after the dissection in both the circumflex femoral arteries in right and left side. Conclusion: Range of origin of PFA was different in other cases and similar in some cases. Feature understanding regarding variations in point of branches, origin of PFA is clinically shown significance and should not be ignored. And the current observation will help to surgeons for the better understanding of variation and anatomical features of PFA.